Association of Staphylococcus aureus in bovine dermatitis - HAZARIKA, R A; MAHANTA, P N; BORAH, P (The Indian Journal of Animal Sciences, 2013)
Staphylococcus aureus was isolated from 45(41.67%) out of 108 cattle suffering from dernatitis.It was involved either singly or in association with other staphylococci, Micrococcus sp., microfilariaand mange-mite. Pathogenicity trial with representative strains and the toxins of the same strains revealed pathogenic and dermonecrotoxic effects on rabbit skin. in-vitro drug sensitivity pattern depicted most sensitivity of the organism to cioxacillin, gentarnicin and chlorampheencol (100% each) and least to streptomycin (64.4).